Women's Autonomy in Batik Workers “Divorce Decision Making” - Muhtarom, Ali; Muhajarah, Kurnia; Dli'fain, Alif Faza (UIN K.H. Abdurrahman Wahid Pekalongan, 2024)
Women today continue to face inferiority. The patriarchal culture prevalent in society generally positions women in a marginalized social status, rendering them vulnerable to violence and exploitation. This results in women lacking control within the household and the absence of autonomous rights. This issue is further exacerbated in the context of divorce cases. This research aims to reveal women's autonomy and the dynamics between husbands and wives in terms of work division and decision-making within the family. This study is a field research that employs a qualitative approach. Collected data were processed and analyzed using an interrelation model. The findings of this study are as follows: First, women's autonomy and power can be realized through access opportunities for women, supported by the existing environmental conditions. Second, in divorce cases, women's autonomy can be assessed through six factors: the absence of spousal responsibility, economic instability, gender awareness, social conditions, ego, and the husband’s lack of motivation to work. Third, the relationship between spouses in work division tends to reflect an equal partnership. Family decision-making, as identified in this study, is characterized by wife-dominant and syncratic decision-making types.